FREQUENCY AND ETIOLOGY OF SPLENOMEGALY IN ADULTS SEEKING MEDICAL ADVICE IN COMBINED MILITARY HOSPITAL ATTOCK - Nadeem, Asif; Ali, Nadir; Hussain, Tasawar; Anwar, Masood (Journal of Ayub Medical College Abbottabad, 2004)
Background: The concept that a palpable spleen can be associated with disease is natural, because this organ normally is not palpable, but may become so under certain circumstances. Questions concerning the frequency, etiology and significance of finding a palpable spleen are raised from time to time. These factors vary with geographical distribution of tropical diseases, and other diseases prevalent in the area. We conducted this study in the department of medicine, at Combined Military Hospital Attock from Sept 2002 to Sept 2003, to find out the frequency and etiology of splenomegaly in our setup. Methods: All patients above the age of 13 years seeking advice of medical specialist in our hospital were included. History and clinical examination was performed and relevant investigations were carried out to establish the diagnosis. Results: 1400 patients were examined. Splenomegaly was present in 96 cases (6.8%). Male to female ratio was 4:1. Eighty-three percent patients had a palpable spleen of 1-5 cm while 8.5% had >10 cm. Different types of anemia constituted 29% of cases, malaria 25%, bacterial infections 18.6% and hematological malignancies 16%. Hepatitis/cirrhosis related splenomegaly was seen in 9.4% cases while 1% had tropical splenomegaly. Conclusion: Different types of anemias, malaria, bacterial infections and hematological malignancies are common causes of splenomegaly in our setup. Splenomegaly should be investigated further since all the common causes are treatable. Keywords: splenomegaly, etiology, adults.